Focus on advanced English C.A.E (Edinburgh Gate, Halow, 1996)
The book is in two distinct parts. Part I develops the language and study skills needed for C.A.E. It also contains four "Language Focu"s sections which provide learner training. Part II concentrates on the requirements of C.A.E and offers systematic practice for each paper. It includes four "Exam Focus" sections.
Keywords: english language - examinations - study guides,english language - textbooks for foreign speakers,test of english as a foreign language - study guides